The Influence of Organizational Commitment, Organizational Culture, and Employee Welfare on Employee Loyalty at the Prosecutorial Commission of the Republic of Indonesia - Purnomo, Hery; Mudjijah, Slamet (Sean Institute, 2025)
This study aims to analyze the influence of organizational commitment, organizational culture, and employee welfare on employee loyalty at the Prosecutorial Commission of the Republic of Indonesia (KKRI). The research is motivated by high employee turnover and the declining sense of belonging among staff. A quantitative approach was used, employing a survey method with a saturated sampling technique involving 40 respondents. Data were collected through a structured questionnaire and analyzed using multiple linear regression. The findings reveal that organizational commitment, organizational culture, and employee welfare each have a positive and significant effect on employee loyalty, both individually and simultaneously. The standardized beta coefficients indicate that organizational commitment has the strongest impact, followed by organizational culture and welfare. The coefficient of determination (R²) shows that 53.1% of the variation in employee loyalty is explained by the three independent variables. These results suggest that strengthening these factors is essential in enhancing employee loyalty in public institutions.